Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan di WE GO PRINT - Nur Al’fiyah; Agung Dwi Nugroho; Tri Wahjoedi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study evaluates the impact of transformational leadership on employee performance at WE GO PRINT. Utilizing a quantitative survey method, data were collected from 120 employees and analyzed using linear regression. The results indicate that transformational leadership, comprising idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, significantly enhances employee performance. Job satisfaction was found to mediate this relationship, while tenure moderated its effect. Practical implications include leadership training, vision communication, innovation promotion, and career development support. This research provides important insights for leadership development and performance enhancement in the digital printing industry.